2012
DOI: 10.1163/187847511x590923
|View full text |Cite
|
Sign up to set email alerts
|

Shading, a View from the Inside

Abstract: Shape from shading arose from artistic practice, and later experimental psychology, but its formal structure has only been established recently by computer vision. Some of its algorithms have led to useful applications. Psychology has reversely borrowed these formalisms in attempts to come to grips with shading as a depth cue. Results have been less than spectacular. The reason might well be that these formalisms are all based on Euclidean geometry and physics (radiometry), which, are the right tools in third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…As a result of the conducted analysis, there have been determined the main conditions in achieving the ecological space, depending on the series of factors: 1) Illumination type -day natural illumination (morning, day, evening, night illumination, dusk) and artificial (directed illumination source, dispersed, reflected); diverse devices of artificial illumination (different by their spectral composition -color light); type of an illumination source: directed (gives the most illuminated form surface with abrupt and deep falling shades); dispersed (creates non-distinct outlines of a form without shades or with hardy perceived ones, that takes place due to the change of the spatial distribution of light intensity); reflected or reverberated (without shades, so the form of subjects is hardly perceived). At that we must take into account the influence of the total force of obscured surfaces (shades) in the general structure of the interior environment, able to change a composition of a coloristic solution [3,7]. Each color has a certain force of light absorption and reflection, depending on its spectral composition and illumination force.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of the conducted analysis, there have been determined the main conditions in achieving the ecological space, depending on the series of factors: 1) Illumination type -day natural illumination (morning, day, evening, night illumination, dusk) and artificial (directed illumination source, dispersed, reflected); diverse devices of artificial illumination (different by their spectral composition -color light); type of an illumination source: directed (gives the most illuminated form surface with abrupt and deep falling shades); dispersed (creates non-distinct outlines of a form without shades or with hardy perceived ones, that takes place due to the change of the spatial distribution of light intensity); reflected or reverberated (without shades, so the form of subjects is hardly perceived). At that we must take into account the influence of the total force of obscured surfaces (shades) in the general structure of the interior environment, able to change a composition of a coloristic solution [3,7]. Each color has a certain force of light absorption and reflection, depending on its spectral composition and illumination force.…”
Section: Resultsmentioning
confidence: 99%
“…[4], but at designing the ecological interior, one must take into account artworks, included in the space. The authors of the paper have revealed, that methods of artworks perception, taking into account the influence of general factors of the space, where they are located, offered by famous scientists Van Assen J. J. R., Wijntjes M., Koenderink J. J., van Doorn A., M. Pont S. [6,7] can be also instruments of increasing the ecology of the space, for example, by illumination means, character of the form structure and coloristics. At that it is explained, that satisfaction of human psychophysiologic needs, reaction to a colorirritative or calming, is connected with a color characteristic, with the notion of tone, brightness, saturation, and also warmth-coldness -color associations that most often depend on subjective characteristics -color advantages, comfort, necessity, expedience of color combinations and general tonality, esthetical influence that is connected with a feeling of beauty and visual ecology of the total space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3D reconstruction, which aims to generate depth information and corresponding surface shapes using the various clues given in the images, is an exciting subject in computer vision. One of the most important clues that provide accurate information about 3D shapes is the spatial pattern of light reflected from surfaces, known as shading [26]- [28].…”
Section: Methodology a Shape From Shadingmentioning
confidence: 99%
“…Note that in computer vision Casorati curvature represents the bending energy of surfaces in E 3 (cf. [73]). The Casorati curvature have been extended to arbitrary submanifolds in Riemannian geometry (cf.…”
Section: Problem 12 Find Simple Relationship Between the Main Extrinmentioning
confidence: 99%